Previous psychiatric disorders in the multistep hypothesis of amyotrophic lateral sclerosis: a South Korean population study. Issue 7 (2nd October 2022) - Choi, Seok-Jin; Park, C. Hyung Keun; Hong, Yoon-Ho; Sung, Jung-Joon
Abstract: Objective: There is accumulating evidence about an association between amyotrophic lateral sclerosis (ALS) and psychiatric disorders. We aimed to investigate the prevalence of previous psychiatric disorders before ALS onset and evaluate the contribution of psychiatric disorders to the number of steps toward developing ALS. Methods: We analyzed the National Health Insurance claims data from 2011 to 2017 and calculated the incidence of ALS. We created a multistep model using the linear least squares method with regression of the log incidence against the log age. Results: The mean annual incidence of ALS was 0.95/100, 000 and frequency of familial ALS (fALS) was 5.89%. The proportions of patients who had psychiatric disorders before ALS diagnosis were 36.8% and 47.0% in fALS and sporadic ALS (sALS), respectively ( p  = 0.009). In both fALS and sALS, depressive disorders and anxiety and stress disorders were relatively frequent, whereas psychotic disorders and bipolar disorders were rare. Further, the slope estimates for regression analyses were 3.50 (R 2 = 0.94) and 3.56 (R 2 = 0.99) for fALS and sALS, respectively, suggesting a 4–5-step process to ALS onset. However, slope estimates did not differ between sALS patients with pre-symptomatic psychiatric disorders and those without. Conclusions: The incidence of ALS is relatively low in Korea and fewer steps are required to develop ALS compared to Western populations (all 6 steps). Although the prevalence of previous depression or anxiety is seemingly high, the multistep model provides no evidence that these conditions modify the risk of developing ALS in our cohort.